Psychometric properties of the new Patients' Expectations Questionnaire - Ann Bowling; Gene Rowe (The Beryl Institute, 2014)
The authors explore the development of the Patients' Expectations Questionnaire (PEQ) and examination of psychometric characteristics it encompasses by reviewing surveys of primary care and hospital outpatients before and after their clinic visit. Three scales were developed for Pre-visit Ideal and Realistic expectations, and Post-visit Experiences (met expectations), based on literature review, semi-structured interviews, and subsequently piloted and refined. Patients completed the questionnaire about their ideal and realistic expectations before they saw the doctor, and were asked if their expectations had been met afterwards. The results show the scales met acceptability criteria for reliability (Cronbach's alphas exceeded α 0.70), administration mode (interview and self-completion), and sample type (general practice and hospital). Split-half reliability was also acceptable. Adjusted odds ratios showed that post-visit experiences (met expectations), followed by feelings of control in life, and age, were the most powerful independent predictors of overall patient satisfaction ratings with the clinic visit, and independent self-ratings of whether their expectations had been met overall. This leads the authors to conclude that the PEQ as a self-report instrument, has good reliability and validity and covers the main types of patient expectations of ambulatory health care. It has policy potential for monitoring expectation management, and is thus of potential benefit to providers and purchasers of health services, and ultimately to patients.